"Coaching" - Form of Effective Organization of Seminar Lessons (Journal of Pedagogical Inventions and Practices, 2022)
In the article, based on my conclusions from the seminar-training organized by the American professor Willie Rolf Hanish, my recommendations are highlighted. Also, the stages of organizing lectures and practical classes and the effective methods used in the educational process are highlighted.